AN EFFECTIVE BEGINNING READING METHOD IN IMPROVING STUDENTS' UNDERSTANDING OF SUBJECTS INDONESIAN LANGUAGE OF CLASS 1 AT UPT SDN 3 WAY KENANGA WEST TULANG BAWANG REGENCY - Siti Bashoriyah Al Qowim; Ulil Azmi (Journal of Higher Education and Academic Advancement, 2024)
The aim of the research is to find the right method to use in teaching beginning reading skills to grade 1 students at SDN 3 Way Kenanga. The aim of beginning reading is also explained in (Depdikbud, 1994:4), namely so that "Students can read simple words and sentences fluently and precisely". The classroom action research (PTK) method was used in this research. The subjects of this research were grade 1 students at SDN 3 Way Kenanga with a total of 27 students consisting of 14 female students and 13 male students. The results of this research are that the syllable method applied in class I at SDN 3 Way Kenanga can actually improve students' initial reading skills. Beginning reading skills can be seen from the average grade in the class which shows an increase from cycle I to cycle II. Observations show that with the implementation of classroom actions in this study almost all students can read simple words, simple sentences and words with consonants. duplicate well and correctly. This can be seen from the average value of 70.92. Before the learning process in the classroom, the teacher should first know the condition of the students and the conditions in the classroom so that they can find out the right method to apply well. Apart from that, teachers are advised to identify the desires and expectations of their students so that they are able to plan appropriate methods to be used in the learning process so that learning objectives can be achieved easily